New Outlooks on Reshaping and Revitalizing Post-Conflict Regions: Strategies, Principles and Models of Reconstruction - Saurabh Bhandari; Tigran Hasic (European Regional Science Association (ERSA), 2001)
Within societies recently recovering from war, people operating at the community or national levels are pressed to deal with reconciliation, development, reintegration and security. Changes and advancements are already at our front door in political philosophy, technology, communications, infrastructure, and shifts in attitudes and behavior of people. All of this will affect regions and communities, and basically alter the requisites for future planning and roles of professionals. Planning in the new millennium is needed to assist people and communities to manage change by all the techniques and skills that it possesses. In progressive crisis situations there is a need for progressive methods and new approaches, especially if the systems in use are not producing necessary results and changes. The situation where the primary objective is the rebuilding of livelihoods and rebuilding a community in a traumatized setting, a holistic way of looking at the ''big picture'' is a condicio sine qua non for any sustainable development effort. The paper draws attention to situations, which require interdisciplinary approaches and the collaboration of different professional actors. In order to structure the complex question of post-conflict reconstruction in a more systematic way, a conceptual interdisciplinary model called Sustainable Communities in Post-Conflict Environments (SCOPE) could be developed for rebuilding communities. This presentation looks at how such a model, applied to places like Bosnia and Herzegovina and Kosovo, can effectively conceptualize and design policies, programs and projects that efficiently address the above-mentioned issues, giving at the same time a new strategic and innovative approach.
Keywords: 330